LOW COST ATAUKAH DIFFERENSIASI? STUDI EMPIRIS IMPLEMENTASI STRATEGI PADA INDUSTRI ADHESIVE DAN SEALANT DI BURSA EFEK INDONESIA - Muslimin Muslimin (Politeknik Negeri Sriwijaya, 2012)
This research aims to test whether low cost and differentiation strategies were implemented partially or simultaneously by the firms in adhesive and sealant industry which listed on Indonesia Stock Exchange. This research also tested whether the firm size is one of the factors which contributed to its performance. The results show that both low cost and differentiation strategies were more effective to implement simultaneously rather than focusing on one strategy. For size’s firm factor, the result proved that it didn’t have any influence to its firm performance when implementing their strategies. Unavailability of research and development fund in the firm budget can be predicted why firm size has no influence to firm’s performance.